Trends in psychological distress during and after the COVID-19 pandemic: Findings from a population-based Costa Rican cohort study - Fantin, Romain Clement (2025)
Objectives The COVID-19 pandemic has resulted in an increase of psychological distress. We hypothesized that the mental health of individuals has improved since the end of the pandemic. Study design 1459 population-based participants of the RESPIRA cohort study (Costa Rica) Methods Psychological distress was measured at 6-month intervals using the Mental Health Inventory 5 (MHI-5) during the 2-year follow-up. Visits occurred between June 2021 and November 2023. Age-sex-standardized MHI-5 mean and proportion of individuals living with psychological distress were estimated by calendar time. We evaluated both cross-sectional estimates over time among all cohort participants, and within-individual evolution among the subset of 1341 participants with repeated measures between June 2021–June 2022 and January–November 2023. Results Standardized prevalence of people living with psychological distress was 13.6 % [10.8–16.8] during the height of the pandemic compared to 8.8 % [6.5–11.6] post-pandemic. The standardized MHI-5 mean increased from 76.3 [74.8–77.9] to 82.9 [81.6–84.3] between the height and post-pandemic periods. 14.5 % of the participants had a much better MHI-5 score (24 points or more) in the post-pandemic period compared to the height of the pandemic, and only 5.3 % had a much worse MHI-5 score. Consistent improvements were observed among sexes and across age, except for 12-17-year-olds. Conclusions This study showed a decrease in the proportion of people living with psychological distress in Costa Rica since the end of the pandemic.